HLA-DO and Its Role in MHC Class II Antigen Presentation - Poluektov, Yuri O.; Kim, AeRyon; Sadegh-Nasseri, Scheherazade (Frontiers in Immunology, 2013)
Helper T cells are stimulated to fight infections or diseases upon recognition of peptides from antigens that are processed and presented by the proteins of Major Histocompatibility Complex (MHC) Class II molecules. Degradation of a full protein into small peptide fragments is a lengthy process consisting of many steps and chaperones. Malfunctions during any step of antigen processing could lead to the development of self-reactive T cells or defective immune response to pathogens. Although much has been accomplished regarding how antigens are processed and presented to T cells, many questions still remain unanswered, preventing the design of therapeutics for direct intervention with antigen processing. Here, we review published work on the discovery and function of a MHC class II molecular chaperone, HLA-DO, in human, and its mouse analog H2-O, herein called DO. While DO was originally discovered decades ago, elucidating its function has proven challenging. DO was discovered in association with another chaperone HLA-DM (DM) but unlike DM, its distribution is more tissue specific, and its function more subtle.